UPAYA PEMBENAHAN PENCATATAN KEUANGAN BUM DESA DEKADE MAJU DI KARANGSALAM, BATURRADEN - Eliada Herwiyanti; Warsidi Warsidi; Agus Faturokhman; Probo Hardini (Jurnal Pengabdian Bisnis dan Akuntansi, 2025)
This community service program aims to improve financial transaction recording at the Dekade Maju Village-Owned Enterprise (BUM Desa) located in Karangsalam, Baturraden. This activity was motivated by the need of the village government and BUM Desa administrators for clearer financial data from the implementation of activities involving culinary business actors in Karangsalam, Baturraden. Coordination between the Community Service Team and BUM Desa Partners resulted in an agreement to solve the problem by providing appropriate tools and technology, including accounting software and adequate hardware for office operations. The tools and technology assistance were handed over to the Partners on July 25, 2025. Subsequently, the Community Service Team provided training and mentoring to the Partners on how to operate the provided tools. The Partners are now able to operate the existing equipment and maintain digital financial records. The community service program has proven to be effective and beneficial for the Partners in improving their financial records. Financial recording at BUM Desa Dekade Maju is now digital, making the resulting financial data easier to understand.